Karakteristik Sensoris dan Mutu Gizi Ikan Masak Kuah Woku (IMAWOKU) dalam Kemasan Kaleng sebagai Pangan Lokal Siap Saji - Hamidin Rasulu; Juharni Juharni; Mila Fatmawati (Universitas Khairun, 2025)
Woku Cooking Fish (IMAWOKU) is a traditional food typical of North Maluku that has a strong taste and great potential to be developed as a ready-to-eat local food product. However, conventional processing has limited shelf life and quality consistency, so packaging innovations are needed that are able to maintain the sensory and nutritional quality of the product. The main problem in the development of IMAWOKU as a ready-to-eat food is how the canning process affects the level of consumer acceptance and the nutritional composition of the product. This study aims to analyze the sensory characteristics and nutritional quality of IMAWOKU in canned packaging as the basis for the development of ready-to-eat local food. The research was carried out in March–August 2025 using a laboratory experimental approach. The main ingredient used is red snapper with typical North Maluku spices. IMAWOKU products are packaged in cans and thermally sterilized. Sensory evaluation was carried out through hedonic tests on 30 semi-trained panelists with attributes of color, aroma, taste, texture, and overall preference. Nutritional quality was analyzed using proximate tests including moisture content, protein, fat, ash, and carbohydrates. The results of organoleptic tests showed that the canned IMAWOKU obtained a high level of likeability, with an average color value of 7.83±0.72 (like–very like), aroma 8.10±0.65 (very like), taste 8.35±0.58 (very like), texture 7.75±0.70 (like), and overall likability 8.20±0.60 (very like). Proximate analysis showed a moisture content of 66.85±1.12%, protein 18.75±0.85%, fat 6.20±0.54%, ash 2.05±0.18%, carbohydrates 6.15±0.92%, and a total energy of 158.4±4.6 kcal/100 g. Based on these results, it can be concluded that canned IMAWOKU has excellent sensory acceptance and balanced nutritional quality, so it has the potential to be developed as a nutritious, practical, and value-added ready-to-eat local food.